2008
DOI: 10.17305/bjbms.2005.3268
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Suicidal Thoughts and Psychoactive Substances

Abstract: In this study is represented the relationship between suicidal thoughts and psychoactive abuse. In study were involved 202 students of Banjaluka's secondary schools. By questioned for risky behaviour of adolescents was found 28.7% of them have suicidal thoughts, and 144 haven't suicidal thoughts. Students from both groups use alcohol but there are not statistically significant differences among groups. The representative sample was 202 students from Banjaluka's secondary schools. The results showed that 28.7% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Licanin et al (2003) [42] discovered that suicidal thoughts were more prevalent among individuals who abused cannabis (50.0%) and those who abused alcohol (36.6%), irrespective of gender or socioeconomic status, in comparison to non-abusers. Another study conducted in Bosnia and Herzegovina confirmed this correlation, particularly among those reporting suicidal ideation, where 36.2% were using cannabis [43].…”
Section: Suicidal Tendenciesmentioning
confidence: 76%
“…Licanin et al (2003) [42] discovered that suicidal thoughts were more prevalent among individuals who abused cannabis (50.0%) and those who abused alcohol (36.6%), irrespective of gender or socioeconomic status, in comparison to non-abusers. Another study conducted in Bosnia and Herzegovina confirmed this correlation, particularly among those reporting suicidal ideation, where 36.2% were using cannabis [43].…”
Section: Suicidal Tendenciesmentioning
confidence: 76%
“…En el presente estudio, se observó que el consumo de Cannabis alguna vez en la vida incrementó el riesgo de suicidio en adolescentes de media vocacional de Santa Marta, Colombia. Este hallazgo es coherente con investigaciones precedentes que evidenciaron que dicho consumo en adolescentes incrementaba la probabilidad de reportar la ideación, el plan y el intento de suicidio (7,8,(36)(37)(38)(39). No obstante, en el estudio de Chabrol, et al, se reportó que el consumo de cannabis no se relacionó con la probabilidad de suicidio (8).…”
Section: Discussionunclassified
“…Yip et al 42 Illicit psychotropic recreational drug use was not considered an important risk factor for suicidal ideation. Spremo and Loga 43 Psychoactive substance use presented an important connection to the presence of suicidal ideation in the adolescents studied.…”
Section: Includedmentioning
confidence: 93%